Nanoscale patterning at the Si/SiO2/graphene interface by focused He+ beam. (6th October 2020) - Böttcher, Artur; Schwaiger, Ruth; Pazdera, Tobias M; Exner, Daniela; Hauns, Jakob; Strelnikov, Dmitry; Lebedkin, Sergei; Gröger, Roland; Esch, Friedrich; Lechner, Barbara A J; Kappes, Manfred M
Abstract: We have studied the capability of He + focused ion beam (He + -FIB) patterning to fabricate defect arrays on the Si/SiO2 /Graphene interface using a combination of atomic force microscopy (AFM) and Raman imaging to probe damage zones. In general, an amorphized 'blister' region of cylindrical symmetry results upon exposing the surface to the stationary focused He + beam. The topography of the amorphized region depends strongly on the ion dose, DS, (ranging from 10 3 to 10 7 ions/spot) with craters and holes observed at higher doses. Furthermore, the surface morphology depends on the distance between adjacent irradiated spots, LS . Increasing the dose leads to (enhanced) subsurface amorphization and a local height increase relative to the unexposed regions. At the highest areal ion dose, the average height of a patterned area also increases as ∼1/ LS . Correspondingly, in optical micrographs, the µ m 2 -sized patterned surface regions change appearance. These phenomena can be explained by implantation of the He + ions into the subsurface layers, formation of helium nanobubbles, expansion and modification of the dielectric constant of the patterned material. The corresponding modifications of the terminating graphene monolayer have been monitored by micro Raman imaging. At low ion doses, DS, the graphene becomes modified by carbon atom defects which perturb the 2D lattice (as indicated by increasing D/G Raman mode ratio). Additional x-ray photoionization spectroscopy (XPS) measurements allow us to infer that for moderate ion doses, scattering of He + ions by the subsurface results in the oxidation of the graphene network. For largest doses and smallest LS values, the He + beam activates extensive Si/SiO2 /C bond rearrangement and a multicomponent material possibly comprising SiC and silicon oxycarbides, SiOC, is observed. We also infer parameter ranges for He + -FIB patterning defect arrays of potential use for pinning transition metal nanoparticles in model studies of heterogeneous catalysis.